Putin's third term as Russia's president, 2012-18 - Black, J. L. (Joseph Laurence), 1937- (New York, N.Y. : Routledge, 2020)
This book provides a comprehensive and systematic overview of Putin's third term as Russia's president. It covers political, international relations, economic and social issues, and provides a balanced assessment of Putin's successes and failures. These include the conflict in Ukraine, the annexation of Crimea, scandals associated with the Olympics, Russia's increasing involvement with Asia, including with the Shanghai Co-operation Organisation, and shifts in the economy away from huge reliance on energy resources. The book sets Putin's activities as president in their wider context, discussing his overall popularity, the weakness of potential opposition and the development of the Russian Federation as a relatively new state.
Introduction -- The presidency -- The Russian Federation : strengths and strains -- The political cockpit -- The Ukraine conundrum -- Economic considerations -- Themes in foreign policy -- Military issues - Quality of life -- Lull before the storm? : concluding remarks.
Reprint. Originally published: 2019.
Keywords: Putin, Vladimir Vladimirovich, -- 1952-; Russia (Federation) -- Foreign relations -- 21st century; Russia (Federation) -- Economic conditions -- 21st century; Russia (Federation) -- Politics and government -- 21st century